Misteri Kristus Dan Kristus Pemersatu Ciptaan Dalam Teologia Filosofis Maximus The Confessor: Sebuah Tinjauan Kritis - Pranoto, Minggus Minarto (Theologia in Loco, 2018)
The incarnation of Christ is the manifestation of God’s love for the creation. God showed the peak of His love and grace in and through the incarnation of Jesus Christ. Through Jesus Christ the Logos, the everything of all good is united and the whole of the creation can achieve the unity with God or experience deification (theosis). The mystery of the incarnation of Christ was revealed byhypostasis union of the two natures of Jesus Christ. The unity of divine and human will (dyotheletism) of Jesus Christ becomes the basis of the unity between God and all creation. The incarnation of Christ, which is the manifestation of God’s love, forms the ultimate aim of the everything of all good. Eventhough, the second person of the Triune God became human being, but it did not mean that there was not secret anymore of the mystery of the incarnation of Jesus Christ. Human being knows the mystery as far it was revealed by God. The incarnation is still a mystery and it can not be explained completely by the mind of human being. In and through Jesus Christ, all creation is integrated into God’s activity or energy, but not with His essence. Maximus can give the basis of the philosophical theology when he discusses the Chalcedonian christology; and his philosophical theology may be able to give a basis for Christian praxis to overcome the problems such as ecology crisis, gender injustice, and fight for human rights.